Research on Discrete Element Numerical Simulation of Loess Landslide under Earthquakes - GUAN Xiaodi (Renmin Zhujiang)
In order to deeply explore the motion and slip laws of loess landslide under earthquake loads,this paper used the discrete element method to numerically simulate the motion of the landslide mass under earthquake loads based on the Heifangtai Landslide in Gansu.The results show that the loess landslide has three parts under the earthquake loads,namely,the source area,the circulation area,and the accumulation area.The residual soil structure in the source area is looser than that before the sliding.In addition,the sliding displacement of particles at different positions near the slope surface in the source area varies greatly.The displacement of particles at the leading edge of the landslide mass is the largest,and that of particles at the trailing edge of the landslide is smaller.As the depth increases,the displacement of particles gradually decreases,and the difference is large.